Rancangan Sistem Informasi Pembayaran Angsuran Rumah oleh Customer Melalui Metode Transfer - Nababan, Maria Del Cielo; Sumarna, Alfonsa Dian (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
This study aims to provide an applied solution related to the problems faced by PT XO, namely the absence of standard information related to the operational procedures for house installment payments for the transfer method, resulting in frequent double payment inputs. The purpose of this study is to compile a house installment payment procedure, both in narrative and flowchart form, and follow good internal control principles. This study uses a qualitative descriptive research method. The results show that the completeness of the documents used in the design of the house installment payment is complete and follows good and correct internal control principles. The conclusion of the study is the design of an operational information system for house installment payments, especially for the transfer method